Context of trust in physicians in singapore: the roles of professional intimacy, physician sexual orientation, and patient sex - Ang, Chin-Siang (2023)
While the general public tends to place trust in medical professionals, little is known about their perceptions of homosexual physicians. Homosexual physicians are often unfairly viewed as less competent, moral, and professional compared to their heterosexual counterparts. The aim of this study was to explore the main and interaction effects of professional intimacy, physician sexual orientation, and patient sex on their ratings of physicians’ trustworthiness. To accomplish this, a web-based survey was conducted using a cross-sectional design. The participants, who also acted as patients in the study, were presented with a series of vignettes depicting three different scenarios involving varying levels of intimacy with either a homosexual or heterosexual physician. The Trust in Physician Scale was employed to assess the degree of trust in physicians. The study included 180 participants from Singapore, with a majority (55.22%) being male and an average age of 34.8 years. The collected data were analyzed using a two-way ANOVA to test the proposed hypotheses. The results indicated that professional intimacy had a significant main effect, while physician sexual orientation did not. Participants appeared to trust physicians the most in situations involving low intimacy, followed by medium and high intimacy scenarios. When focusing specifically on the homosexual physician condition, there was a noteworthy interaction between professional intimacy and the sex of the patient in relation to the variability of trust. Male participants, compared to female participants, tended to trust physicians more in scenarios with medium intimacy rather than high intimacy, while the reverse was true for females. These findings shed light on the contemporary and understudied topic of attitudes toward homosexual physicians in Singapore’s healthcare system.